2014
DOI: 10.1007/s11999-014-3719-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Development of Heterotopic Ossification After Acetabular Fracture Fixation

Abstract: Background Heterotopic ossification (HO) is a common complication of the operative treatment of acetabular fractures. Although the surgical approach has been shown to correlate with the development of ectopic bone, specific risk factors have not been elucidated. Questions/purposes The purposes of this study were to determine specific risk factors associated with the development of severe HO and the frequency with which patients develop severe HO after acetabular fracture fixation through an isolated Kocher-Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 24 publications
6
61
0
3
Order By: Relevance
“…Although some studies support prophylaxis in high-risk patients [4,6,10,21], there is currently no consensus as to which prophylactic measure is the most efficacious. Previous studies have demonstrated the value of gluteus minimus débridement in reducing the risk of HO and compared its effectiveness with that of indomethacin [10,20,22]. To our knowledge, this is the first study comparing the effectiveness of gluteus minimus débridement with and without radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although some studies support prophylaxis in high-risk patients [4,6,10,21], there is currently no consensus as to which prophylactic measure is the most efficacious. Previous studies have demonstrated the value of gluteus minimus débridement in reducing the risk of HO and compared its effectiveness with that of indomethacin [10,20,22]. To our knowledge, this is the first study comparing the effectiveness of gluteus minimus débridement with and without radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with fewer than 10 weeks followup (n = 12) were excluded, because several studies [10,19,20] suggest that most HO that develops is visible by that point in time. Three of 27 patients in the radiotherapy and débridement group were excluded for insufficient followup and nine of 31 patients in the débridement-only group were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Posterior approaches for acetabular surgery, such as the Kocher‐Langenbeck approach, increase the risk of HO formation in the gluteus minimus muscle. This has been demonstrated by a decreased incidence of HO when necrotic gluteus minimus tissue is debrided after acetabular fracture fixation 4, 5. The upper extremity is also affected, especially following surgical approaches about the elbow.…”
Section: Injuries and Surgeriesmentioning
confidence: 99%